2009
DOI: 10.1111/j.1468-1293.2009.00728.x
|View full text |Cite
|
Sign up to set email alerts
|

Boosted protease inhibitors as a therapeutic option in the treatment of HIV‐infected children

Abstract: Objective Paediatric HIV treatment must address various special considerations. Administration of pharmacokinetically enhanced protease inhibitors (PIs) can improve paediatric therapeutic outcomes. The objective of this study was to review the use of boosted PI regimens in children. Methods Systematic literature searches of published manuscripts and conference databases using generic drug names and specific keywords were performed to ensure thorough and balanced reporting of available data. Results Boosted PI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…The impact of DRMs acquired via prevention of mother-to-child transmission could not be evaluated in our study, but we previously reported a moderate (between 5% and 15%) prevalence of DRMs in the Central African HIV-infected pediatric population of Bangui. [96] These observations support the use of lopinavir-based 1st-line regimens in children in Africa as recommended by the WHO, [7,8,46,82,85,90,97] especially with the recent national recommendations to implement lifelong antiretroviral treatment for mothers. However, only 1 (12.5%) of the 8 children aged below 5 years was on a 1st-line PI-based antiretroviral treatment regimen in 2013 as recommended by the WHO, illustrating that these guidelines have not yet been implemented.…”
Section: Discussionsupporting
confidence: 59%
“…The impact of DRMs acquired via prevention of mother-to-child transmission could not be evaluated in our study, but we previously reported a moderate (between 5% and 15%) prevalence of DRMs in the Central African HIV-infected pediatric population of Bangui. [96] These observations support the use of lopinavir-based 1st-line regimens in children in Africa as recommended by the WHO, [7,8,46,82,85,90,97] especially with the recent national recommendations to implement lifelong antiretroviral treatment for mothers. However, only 1 (12.5%) of the 8 children aged below 5 years was on a 1st-line PI-based antiretroviral treatment regimen in 2013 as recommended by the WHO, illustrating that these guidelines have not yet been implemented.…”
Section: Discussionsupporting
confidence: 59%
“…7,[11][12][13][14]20,[25][26][27][28][29][30] Furthermore, the rate of therapeutic failure appears greater when NNRTI-based regimens are used as a first-line treatment, and then ranges from 20% to 75%, 7,[11][12][13][14]20,25,28,29 compared to when a PI-based regimen is used (range: 26-36%). 26,27 In the series of children reported here, who were prescribed mostly with a first-line ARV treatment, including NNRTI, virological failure was frequently associated with major NNRTI-resistance mutations, whereas no major PI-resistance mutations were observed in children treated by firstline PI therapy.…”
Section: Discussionmentioning
confidence: 96%
“…These observations emphasize the possibility of using PI more frequently as a pediatric first-line regimen in Africa. 20,30 In particular, the use of an LPV-based treatment could be of interest because of the frequent transmitted drug resistance to NNRTI caused by the common use of single-dose NVP to prevent HIV mother-to-child transmission in subSaharan Africa. In addition, there is a higher rate of virological success in PI-treated children versus NNRTI-treated children.…”
Section: Discussionmentioning
confidence: 99%
“…Children who started LPVr were switched to a NVP-based regimen after achieving virological suppression. To facilitate dose calculations, we used weight band-based dosing of paediatric LPVr tablets (100 mg/25 mg) to achieve an approximate dose of 300 mg/m 2 /dose (10–20 kg, 2-0-2; 20–30 kg, 3-0-3; >30 kg, 4-0-4) [16], [17]. Paediatric LPVr tablets were substituted by larger adult tablets (200 mg/50 mg) if the child was able to swallow them (in these cases, the dosing in the 20–30 kg band was 2-0-1 adult tablets).…”
Section: Methodsmentioning
confidence: 99%